The response to whistleblowing by regulators: a practical perspective - Savage, Ashley; Hyde, Richard (Wiley, 2014)
The Public Interest Disclosure Act 1998 provides protection for whistleblowers; it does not place statutory obligations on regulators to act in response to whistleblowing concerns. Using Freedom of Information requests as a research methodology, this paper seeks to examine how whistleblowing is approached by regulators and what happens when a whistleblowing disclosure is made. Forty-eight national regulators in a variety of fields and 408 county, district and unitary local authorities with responsibility for the regulation of food were contacted. The paper begins by considering the importance of whistleblowing disclosures and how they are protected in PIDA. The examination of the law reveals that several organisations with important regulatory functions are not prescribed, and this has the potential to create inconsistencies in the protection of whistleblowers. The bulk of the paper examines the results of the Freedom of Information requests. By examining the results of these requests, it was possible to show that there are a number of inconsistencies in the way in which regulatory agencies handle concerns. Several changes to practice are suggested in order to ensure that the whistleblowers receive appropriate treatment and that the concerns that they express can be properly addressed.